BS EN 16272-3-2. Railway applications. Infrastructure. Noise barriers and related devices acting on airborne sound propagation. Test method for determining the acoustic performance. Part 3-2. Normalized railway noise spectrum and single number ratings for direct field applications (17th February 2022) - British Standards Institution,
No abstract available